Direct visualization of local interaction forces in Bi2Sr2CaCu2O8+δ vortex matter - Aragón Sánchez, J.; Cortés Maldonado, R.; Dolz, M.I.; CejasBolecek, N.R.; van der Beek, C.J.; Konczykowski, M.; Fasano, Y.; Fasano, Yanina (Elsevier, 2019)
Fil: Aragón Sánchez, J. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina